Mobile-assisted academic vocabulary learning with digital flashcards: Exploring the impacts on university students’ self-regulatory capacity - Boroughani, Tahereh; Behshad, Nastaran; Xodabande, Ismail (Frontiers in Psychology, 2023)
The current study aimed to investigate the contribution of mobile-assisted vocabulary learning with digital flashcards in scaffolding academic vocabulary learning and self-regulatory capacity development among university students. The participants were 54 Iranian university students selected based on their availability in the study context. The participants were assigned to an experimental group (N = 33) and a control learning condition (N = 21). Those in the experimental group used digital flashcards (i.e., Quizlet) to learn academic words in a recently developed core academic wordlist (i.e., NAWL), and the control group used traditional materials (wordlists) to learn the same vocabulary items. The participants' vocabulary knowledge and self-regulatory capacity for vocabulary learning were tested before and after the treatments. The findings indicated that although both groups improved their vocabulary knowledge and self-regulatory capacity after four months, the experimental group outperformed the control group in both measures, and the effect sizes of the observed differences were very large. Consequently, the study provided empirical evidence for the effectiveness of mobile-assisted vocabulary learning over traditional materials in developing academic literacy and indicated that using digital flashcards for vocabulary learning improves university students' capacity for undertaking self-regulated vocabulary learning. The implications of these findings for EAP programs are highlighted.